Determining the effect of plasmochemically activated aqueous solutions on the bioactivation process of sea buckthorn seeds - Kovalova, Olena; Ковальова, Олена Сергіївна; Vasylieva, Natalia; Васильєва, Наталія Костянтинівна; Stankevych, S.; Станкевич, С. В.; Zabrodina, I.; Забродіна, І. В.; Haliasnyi, I.; Галясний, І. В.; Gontar, T.; Гонтар, Т. Б.; et al. (Український державний університет залізничного транспорту, 2023)
The studies revealed the regularities of obtaining bioactivated sea buckthorn seeds using plasmachemically activated aqueous solutions during germination. Sea buckthorn seeds were chosen as the research object. Plasma-chemically activated aqueous solutions were used to activate the germination process. This made it possible to solve the problem of processing waste from the production of sea buckthorn oil, and also contributed to obtaining a high-quality component of food products. Experimental studies have proven the effectiveness of using plasmachemically activated aqueous solutions as effective intensifiers and disinfectants for the process of bioactivation of sea buckthorn seeds. It is shown that their use intensifies the germination of sea buckthorn seeds, contributes to a more active accumulation of biologically valuable components in the seeds. Plasmachemically activated aqueous solutions with a peroxide concentration of 300– 700 mg/l were used. An increase in the geometric parameters of seeds, namely length by 8.5–14.9 % and width by 3.7– 14.8 %, was recorded. The germination energy increased by 5–13 % and germination capacity by 5–14 %. The composition of sea buckthorn seeds, both derived raw material and bioactivated, was investigated. Studies have shown that bioactivated seeds contain an increased amount of highly valuable substances. The protein content increased by 4 % compared to sea buckthorn seeds and by 1.7 % compared to the control. The lipid content increased by 2 and 1.1 %. An increase in the content of vitamins was noted: B1, B2, C, A, E, R. The amount of amino acids increased by 9–13 % compared to the control, and compared to the original raw material – by 1.5–3.5 times. In addition, plasmachemically activated aqueous solutions effectively disinfected the raw material. The presented technology can be used in the food processing industry. Проведеними дослідженнями встановлені закономірності отримання біоактивованого насіння обліпихи з використанням при пророщуванні плазмохімічно активованих водних розчинів. Об’єктом дослідження було обрано насіння обліпихи. Для активації процесу проростання застосували плазмохімічно активовані водні розчини. Це дозволило вирішити проблему переробки відходів виробництва обліпихової олії, а також сприяло отриманню високоякісного компонента харчових продуктів. Експериментальними дослідженнями доведена ефективність використання плазмохімічно активованих водних розчинів, як дієвих інтенсифікаторів і дезінфектантів процесу біоактивації насіння обліпихи. Показано, що їх застосування дозволяє інтенсифікувати пророщування насіння обліпихи, сприяє більш активному накопиченню біологічно цінних складових в насінні. Використовували плазмохімічно активовані водні розчини з концентрацією пероксидів 300–700 мг/л. Зафіксовано збільшення геометричних показників насіння, а саме довжини на 8,5–14,9 %, та ширини на 3,7–14,8 %. Підвищились енергія проростання – на 5–13 % та здатність до проростання – на 5–14 %. Був досліджений склад насіння обліпихи, як похідної сировини, так і біоактивованої. Дослідження показали, що біоактивоване насіння має в своєму складі підвищену кількість високоцінних речовин. Вміст білків в порівнянні з насінням обліпихи збільшився на 4 % і в порівнянні з контролем на 1,7 %. Вміст ліпідів підвищився на 2 і на 1,1 %. Відмічено збільшення вмісту вітамінів: В1, В2, С, А, Е, Р. Кількість амінокислот зросла на 9–13 % у порівнянні з контролем, а в порівнянні з вихідною сировиною – в 1,5–3,5 рази. Крім того, плазмохімічно активовані водні розчини якісно продезінфікували сировину. Представлена технологія зможе знайти застосування в харчопереробній галузі.
Виявлення впливу плазмохімічно активованих водних розчинів на процес біоактивації насіння обліпихи
Keywords: processing of sea buckthorn seeds; переробка насіння обліпихи; plasma-chemical activation; плазмохімічна активація; aqueous solutions; водні розчини; germinated seeds; пророщене насіння; biologically active substances; біологічно-активні речовини